KEBERHASILAN TERAPI OKRONOSIS EKSOGEN DENGAN LASER PICOSECOND (PICO) PADA PASIEN WANITA USIA 65 TAHUN: LAPORAN KASUS - Irdawaty Izrul (Nusantara Hasana Journal, 2025)
Exogenous ochronosis (EO) is a rare but challenging hyperpigmentation disorder, usually associated with long-term hydroquinone use and chronic sun exposure. Treatment is often difficult, and conventional therapies frequently yield unsatisfactory results. We report a 65-year-old woman with darkened facial skin following prolonged hydroquinone. The patient presented with diffuse bluish-brown hyperpigmentation over the malar and mandibular regions. She was treated exclusively with monthly pico laser therapy. After 10 sessions, a significant clinical improvement was observed, with marked reduction of pigmentation and satisfactory cosmetic outcome, without major side effects. Pico laser delivers ultra-short pulses with high peak power, inducing photoacoustic effects that selectively target melanin without damaging surrounding tissues. In this case, pico laser demonstrated high efficacy in reducing pigmentation in exogenous ochronosis, where other modalities such as topical depigmenting agents or chemical peels are often ineffective. This result suggests pico laser as a promising therapeutic option for difficult-to-treat pigmentary disorders, especially in elderly patients. This case highlights the successful application of pico laser for treating exogenous ochronosis with significant improvement after 10 treatment sessions, underscoring its role as a safe and effective therapeutic option.